2019
DOI: 10.1002/jcp.29420
|View full text |Cite
|
Sign up to set email alerts
|

Switches in histone modifications epigenetically control vitamin D3‐dependent transcriptional upregulation of the CYP24A1 gene in osteoblastic cells

Abstract: In bone cells vitamin D dependent regulation of gene expression principally occurs through modulation of gene transcription. Binding of the active vitamin D metabolite, 1,25‐dihydroxy vitamin D3 (1,25(OH)2D3) to the vitamin D receptor (VDR) induces conformational changes in its C‐terminal domain enabling competency for interaction with physiologically relevant coactivators, including SRC‐1. Consequently, regulatory complexes can be assembled that support intrinsic enzymatic activities with competency to posttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…Overall, the applied algorithms revealed nine specific proteins for the osteoblastic differentiation, respectively. Analogous to BGN, cytochrome P450 family 24 subfamily A member 1 (CYP24A1), AE binding protein 1 (AEBP1), and collagen type III alpha 1 chain (COL3A1) concern functions of bone mineralization, osteoblastogenesis as well as matrix remodeling and thus confirmed a close association to the osteoblastic molecular differentiation module [ 56 , 57 , 58 , 59 , 60 ]. Strikingly, CYP24A1 presented the highest fold-change comparing OB to MSC (log 2 FC 3.65) and OB to AD (log 2 FC 3.52).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the applied algorithms revealed nine specific proteins for the osteoblastic differentiation, respectively. Analogous to BGN, cytochrome P450 family 24 subfamily A member 1 (CYP24A1), AE binding protein 1 (AEBP1), and collagen type III alpha 1 chain (COL3A1) concern functions of bone mineralization, osteoblastogenesis as well as matrix remodeling and thus confirmed a close association to the osteoblastic molecular differentiation module [ 56 , 57 , 58 , 59 , 60 ]. Strikingly, CYP24A1 presented the highest fold-change comparing OB to MSC (log 2 FC 3.65) and OB to AD (log 2 FC 3.52).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on the distinct functions of PRMT1, PRMT4/CARM1 and PRMT5 complement and extend previous studies that examined the contribution of PRMTs and their cognate epigenetic modifications in vitamin D3-dependent transcriptional regulation in rat osteosarcoma cells. One previous study showed that PRMT1 and PRMT4/CARM1 support the vitamin D3 (1,25(OH) 2 D 3 ) dependent upregulation of CYP24A1 gene expression ( Moena et al, 2020b ). Examination of histone marks revealed that H4R3me2a and H3R17me2a and their corresponding writers PRMT1 and PRMT4, respectively, are recruited by vitamin D receptor (VDR) and its coactivator SRC-1/NCOA1.…”
Section: Discussionmentioning
confidence: 99%
“…PRMT1, PRMT4/CARM1, PRMT5 and PRMT7 are prevalent isoforms that are functionally expressed in myogenic cells and osteosarcoma cells ( Moena et al, 2020a ; Blanc and Richard, 2017 ; Rakow et al, 2020 ). Three PRMTs (i.e., PRMT1, PRMT4/CARM1 and PRMT5) have each been shown to control vitamin D3-dependent transcription in osteosarcoma cells via interactions with SRC-1/NCOA1 ( Moena et al, 2020b ), whereas PRMT5 binds to the SWI/SNF component BRG1/SMARCA4 in different cell types ( Seth-Vollenweider et al, 2014 ). These findings collectively suggest that PRMT proteins may also have a role in osteoblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, several groups have examined the presence and function of epigenetic posttranslational modifications in chromosomal histone proteins that are associated with the CYP24A1 gene promoter (Fetahu et al, 2014;Meyer, Goetsch, & Pike, 2010b;Moena et al, 2020;Seth-Vollenweider et al, 2014). Our team has reported that specific transitions in enrichments of epigenetic histone marks accompany transcriptional upregulation of the CYP24A1 gene in osteoblastic cells exposed to 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 99%